Surgical treatment of hepatic hydatid cysts - (:unkn) unknown (My University, 1989)
This is a retrospective study of 44 surgical cases of hepatic hydatid cysts. The most common procedure was omentoplasty in 26 patients (55.3%), 10 with omentoplasty alone and 16 combined with partial cystectomy and tube drainage. The second most common procedure was external tube drainage in 15 (32.0%), where complication rates were higher (73.3%) than omentoplasty (15.4%). The most controversial aspect of hydatid surgery is the management of the cyst cavity. The major advantage of omentoplasty is that it is easy to perform and it is the best way to obliterate the remaining cavity. Hospitalization was shortest for omentoplasty. There was no mortality.